2007
DOI: 10.2139/ssrn.1017476
|View full text |Cite
|
Sign up to set email alerts
|

Welfare and Distribution Effects of Water Pricing Policies

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 70 publications
0
10
0
3
Order By: Relevance
“…Depending on the way water is perceived and the societal structure, different payment and subsidy systems have been used. Welfare effects of block tariffs and flat rates have been investigated in Mauritius (Madhoo, 2011), São Paulo (Ruijs, 2007) and Manaus (Olivier, 2010), while Gomez-Lobo et al (2000) considered water-subsidy schemes in Latin America. Gawel et al (2013) compared different approaches to measure affordability.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the way water is perceived and the societal structure, different payment and subsidy systems have been used. Welfare effects of block tariffs and flat rates have been investigated in Mauritius (Madhoo, 2011), São Paulo (Ruijs, 2007) and Manaus (Olivier, 2010), while Gomez-Lobo et al (2000) considered water-subsidy schemes in Latin America. Gawel et al (2013) compared different approaches to measure affordability.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the complexities of the regulatory process involved in setting water price levels and water tariff structures, water charges may not end up being equitably distributed among income groups and access to even basic amounts of water might be very unequal among even citizens of the same country (e. g. Ruijs et al, 2008;Ruijs, 2009). In fact, water affordability is a significant problem in both developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Chipman and Moore (1980) showed that CV adequately compares alternative pricing policies in the case of homothetic preferences and changes in price but not in income. However, as discussed by Ruijs (2009), a change in price also generates changes in virtual income when analyzing the effects of alternative IBR tariffs.…”
Section: Demand and Welfare Estimation Under Non-linear Pricingmentioning
confidence: 99%